2018
DOI: 10.3390/cryst8070294
|View full text |Cite
|
Sign up to set email alerts
|

Small Polaron Hopping in Fe:LiNbO3 as a Function of Temperature and Composition

Abstract: Small-polaron hopping involved in charge transport in Fe-doped congruent lithium niobate is investigated as a function of temperature and composition by means of light-induced transient absorption spectroscopy. The relaxation dynamics of the light-induced polaron population is characterized by individual activation energies within different temperature ranges. A numerical investigation carried out by Monte Carlo simulations reveals that these findings may be understood in terms of the varying abundance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
4
15
0
1
Order By: Relevance
“…This is consistent with the fact that energy level of Fe traps is significantly lower than the bipolaron one (1.92 eV with respect to 1.07 eV, respectively [13]), so that migrating polarons tend to move to Fe traps instead of forming bipolarons. The absence of bipolarons in Fe:LN samples is also corroborated by the observation that in LIA experiments there is no evidence of an increased absorption in the blue spectral region, as it would be the case upon bipolaron formation [26]. (ii) Trap saturation effects are negligible, so that we can assume that the trap concentrations are constant.…”
Section: Monte Carlo Simulation Of Polaron Hoppingsupporting
confidence: 54%
“…This is consistent with the fact that energy level of Fe traps is significantly lower than the bipolaron one (1.92 eV with respect to 1.07 eV, respectively [13]), so that migrating polarons tend to move to Fe traps instead of forming bipolarons. The absence of bipolarons in Fe:LN samples is also corroborated by the observation that in LIA experiments there is no evidence of an increased absorption in the blue spectral region, as it would be the case upon bipolaron formation [26]. (ii) Trap saturation effects are negligible, so that we can assume that the trap concentrations are constant.…”
Section: Monte Carlo Simulation Of Polaron Hoppingsupporting
confidence: 54%
“…Also, it is reported that, in LN:Fe, the charge transportation through polaron hopping of electron/holes is slow and is processed on Li-sites due to the presence of Nb Li defects. It was suggested that in the absence of the antisites Nb, the hopping transport is shifted to the Nb sites and is much faster than chaotic Li-sites [42,43,44]. Therefore, doping V and Zr with Fe ions changes the hopping transport to Nb sites by reducing the Nb Li sites and does not disturb the usual lithium site occupation of Fe and instead helps in eliminating the undesired intrinsic traps as shown in Figure 5b.…”
Section: Discussionmentioning
confidence: 99%
“…The decay of this photo-induced absorption is attributed to their recombination with p-type small polarons that are bound to lithium vacancies, O − −V Li . This attribution is supported by evidence of only negligible Fe and Nb Li contamination in these crystals [17]. Indeed, room-temperature transient absorption measurements on a series of Mg-doped and nominally pure LN samples by Conradi et al [26] also concluded that the primary signal at 785 nm stems from Nb 4+ free small polarons.…”
Section: Combining the Decay Of Lithium Niobate's Induced Absorption mentioning
confidence: 87%
“…Our optical excitation then primarily produces free Nb 4+ n-type small polarons and O − -V Li sites, p-type polarons bound to lithium vacancies [25,26]. We thereby avoid the profusion of other types of polaron states that occur in materials such as Fe:LN [17,27]. The transient near infra-red absorption in LN is primarily due to small polarons [6,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation